Anaemic retinopathy in megaloblastic anaemia (Nepalese Journal of Ophthalmology, 2020)
Introduction: Anaemias are the commonest haematological disorders which cause ocular manifestations. With the progression of disease, retinal haemorrhages, dilated and tortuous veins, cotton wool spots may occur in the ocular fundus.Case: An 18-year-old female patient presented to our out patient department with the sudden, painless, non-progressive blurring of vision in both eyes (best-corrected visual acuity in the right eye is 6/60, and left eye is 6/36) for two days. On Ophthalmological examination, bilateral pale tarsal conjunctiva, yellowish discolouration of the sclera, hyperemic optic discs, macular haemorrhages, superficial and deep haemorrhages with Roth spots were observed. The haematological evaluation showed the presence of Megaloblastic anaemia (with haemoglobin - 2.5g%). There was severe pallor on general examination. Mild hepatomegaly and splenomegaly were noted on the systemic examination and confirmed by ultrasound abdomen. Intraocular pressure was 11 mmHg in both eyes.Conclusion: This case documents the occurrence of bilateral macular haemorrhages and Roth spots in megaloblastic anaemia without thrombocytopenia. Other causes of Roth spots were excluded. Treatment of anaemia showed resolution of Roth spots.